Češi v zemi beze jména - Svoboda, David (Lidé města, 2005)
In the period following the Austro-Hungarian Settlement, Ruthenians were mentioned quite infrequently in the Czech printed media. Shortly before the First World War this situation had changed. Our public followed with displeasure the infamous so called Marmaros Trial that was unleashed by the former Hungarian authorities as part of the campaign against Ruthenian Orthodoxy. The first mass contact between the Czechs and Ruthenians, signaling a long-term co-existence, took place in January 1919 when the first Czechoslovak soldiers entered the land of the present Subcarpathian Ruthenia.